Gospoda-tovarishchi . Gospoda-tovarishchi . Gentlemen-Comrades . Господа-товарищи - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the political situation in Russia; dissolution of the Supreme Soviet of the Russian Federation. Featured in the program: Afanas'ev, IUrii (Rector of the Russian State University of Humanities); Rogozin, Dmitrii (Politician); Bokan', IUrii (Politician) Contributors: Omel'ianiuk, Ol'ga (Anchor) Обсуждение политической ситуации в России; роспуск Верховного Совета Российской Федерации. В программе участвуют: Афанасьев, Юрий (Ректор Российского государственного гуманитарного университета); Рогозин, Дмитрий (Политик); Бокань, Юрий (Политик) Создатели: Омельянюк, Ольга (Ведущий/Ведущая)